Kontrol Adaptif Referensi Model untuk Netralisasi pH dalam Pengolahan Air Limbah Batik - Nazuwatussya'diyah Nazuwatussya'diyah; Estiyanti Ekawati; Justin Pradipta (Pusat Teknologi Instrumentasi dan Otomasi (PTIO) - Institut Teknologi Bandung, 2026)
The batik industry generates wastewater with elevated pH levels due to sodium hydroxide usage in dyeing processes, frequently exceeding the regulatory standard of pH 6–9. Traditional dilution methods prove economically inefficient, necessitating more adaptive control strategies. This research designs and simulates a nonlinear adaptive control system based on Model Reference Adaptive Control (MRAC) for pH neutralization using acetic acid. The Continuous Stirred Tank Reactor (CSTR) mathematical model was developed from mass balance, acid-base equilibrium, and electroneutrality principles, then simulated using Ordinary Differential Equation (ODE) functions in MATLAB. MRAC performance was compared with conventional PI controller across various initial wastewater pH conditions. Simulation results demonstrate that MRAC achieves faster convergence, reaching pH 7 in 2488.68 seconds from initial pH 9, compared to PI controller (3080.96 seconds) or uncontrolled system (10225 seconds). With settling time of 2377 seconds versus 2566.4 seconds for PI, MRAC reduces neutralizer consumption by 0.61% (9.5380 L versus 9.5969 L) while maintaining safety criteria above the lower pH bound of 6.80. Lyapunov stability analysis confirms the asymptotic stability of the adaptive controller. This study demonstrates that MRAC offers superior performance for batik wastewater pH control while reducing dependency on uneconomical dilution methods.